Celecoxib activates autophagy by inhibiting the mTOR signaling pathway and prevents apoptosis in nucleus pulposus cells - Weisin Chen; Miersalijiang Yasen; Hanquan Wang; Chenyang Zhuang; Zixiang Wang; Shunyi Lu; Libo Jiang; Hong Lin (BMC, 2022)
Abstract Background Intervertebral disc degeneration results from a variety of etiologies, including inflammation and aging. Degenerated intervertebral discs feature down-regulated extracellular matrix synthesis, resulting in losing their ability to retain water and absorb compression. Celecoxib is a well-known selective cyclooxygenase-2 inhibitor for treating arthritis and relieving pain. Nevertheless, the mechanism of Celecoxib for treating inflammation-related intervertebral disc degeneration has not yet been clarified. Method Protein synthesis was analyzed by western blot. Fluorescent probes DCFH-DA and MitoSox Red detected reactive oxygen species and were measured by flow cytometry. The activity of the kinase pathway was evaluated by protein phosphorylation. Autophagy was monitored by mRFP-GFP-LC3 transfection and LC3 analysis. Mitochondrial apoptotic proteins were analyzed by western blot and cell membrane integrity was measured by flow cytometry. The autophagic gene was silenced by siRNA. Results In this study, interleukin-1β stimulation reduced the synthesis of aggrecan, type I and II collagen and caused excessive production of reactive oxygen species. We looked for a therapeutic window of Celecoxib for nucleus pulposus cells to regain extracellular matrix synthesis and reduce oxidative stress. To look into nucleus pulposus cells in response to stimuli, enhancement of autophagy was achieved by Celecoxib, confirmed by mRFP-GFP-LC3 transfection and LC3 analysis. The mammalian target of rapamycin and a panel of downstream proteins responded to Celecoxib and propelled autophagy machinery to stabilize homeostasis. Ultimately, inhibition of autophagy by silencing autophagy protein 5 disrupted the protective effects of Celecoxib, culminating in apoptosis. Conclusion In summary, we have demonstrated a new use for the old drug Celecoxib that treats intervertebral disc degeneration by enhancing autophagy in nucleus pulposus cells and opening a door for treating other degenerative diseases.